Hypertext Complements Print? A Study Of Narrative Reconfiguration In Geoff Ryman's Novel 253 - Ling, Chung Guan (2011)
Despite the concern that print books will soon become obsolete by the advancement of the digital media, there is an increasing attempt by authors to bring traditional storytelling into new dimensions. This is done by incorporating the hypertext technique in the book form with the hope that a new narrative experience offered by the digital media can similarly be enjoyed in print. However, the effort to blend some of the intrinsic qualities of hypertext within the book‟s materiality requires careful consideration. This study examines the extent to which the digital medium and the print medium complement each other in storytelling based on Geoff Ryman‟s hypertext novel 253 which is first written for the computer before being converted into book. To illustrate each medium‟s capability in telling the same story, the narrative architectures that are represented in both media are analysed and cross-examined through an analytical model that is derived from various interdisciplinary analyses of narratology along with various theoretical perspectives on hypertext. The comparative analysis of the two versions revealed that the book form mainly used the index method as a substitute to hypertext linking. This simple reconfiguration had nevertheless helped maintain the story-level and discourse-level of the narrative. The novel‟s thematic concerns and several hypertext concepts were also successfully preserved. However, the intrinsic qualities of hypertext namely the connectivity, ease of navigation, and interactivity were unable to be similarly reproduced due to the book‟s materiality factor. These results suggest that the two media could complement each other only to a certain level, but for the blending of hypertextuality in book storytelling to be more successful, authors must find an equivalent to the three qualities of hypertext in their writing.